Effect of Diameter and Number of Hepatocellular Carcinomas on Survival After Resection, Transarterial Chemoembolization, and Ablation. (21st August 2021) - Kawaguchi, Yoshikuni; Hasegawa, Kiyoshi; Hagiwara, Yasuhiro; De Bellis, Mario; Famularo, Simone; Panettieri, Elena; Matsuyama, Yutaka; Tateishi, Ryosuke; Ichikawa, Tomoaki; Kokudo, Takashi; Izumi, Namiki; Kubo, Shoji; et al.
Abstract : INTRODUCTION: Most studies predicting survival after resection, transarterial chemoembolization (TACE), and ablation analyzed diameter and number of hepatocellular carcinomas (HCCs) as dichotomous variables, resulting in an underestimation of risk variation. We aimed to develop and validate a new prognostic model for patients with HCC using largest diameter and number of HCCs as continuous variables. METHODS: The prognostic model was developed using data from patients undergoing resection, TACE, and ablation in 645 Japanese institutions. The model results were shown after balanced using the inverse probability of treatment-weighted analysis and were externally validated in an international multi-institution cohort. RESULTS: Of 77, 268 patients, 43, 904 patients, including 15, 313 (34.9%) undergoing liver resection, 13, 375 (30.5%) undergoing TACE, and 15, 216 (34.7%) undergoing ablation, met the inclusion criteria. Our model (http://www.u-tokyo-hbp-transplant-surgery.jp/about/calculation.html ) showed that the 5-year overall survival (OS) in patients with HCC undergoing these procedures decreased with progressive incremental increases in diameter and number of HCCs. For patients undergoing resection, the inverse probability of treatment-weighted-adjusted 5-year OS probabilities were 10%–20% higher compared with patients undergoing TACE for 1–6 HCC lesions <10 cm and were also 10%–20% higher compared with patients undergoing ablation when the HCC diameter was 2–3 cm. For patients undergoing resection and TACE, the model performed well in the external cohort. DISCUSSION: Our novel prognostic model performed well in predicting OS after resection and TACE for HCC and demonstrated that resection may have a survival benefit over TACE and ablation based on the diameter and number of HCCs. Abstract :